Complement in the Pathophysiology of the Antiphospholipid Syndrome - Chaturvedi, Shruti; Brodsky, Robert A.; McCrae, Keith R. (Frontiers in Immunology, 2019)
The antiphospholipid syndrome (APS) is characterized by thrombosis and pregnancy morbidity in the presence of antiphospholipid antibodies (aPL). Complement is a system of enzymes and regulatory proteins of the innate immune system that plays a key role in the inflammatory response to pathogenic stimuli. The complement and coagulation pathways are closely linked, and expanding data indicate that complement may be activated in patients with aPL and function as a cofactor in the pathogenesis of aPL-associated clinical events. Complement activation by aPL generates C5a, which induces neutrophil tissue factor-dependent procoagulant activity. Beta-2-glycoprotein I, the primary antigen for pathogenic aPL, has complement regulatory effects in vitro; moreover, aPL induce fetal loss in wild-type mice but not in mice deficient in specific complement components (C3, C5). Antiphospholipid antibodies also induce thrombosis in wild type mice and this effect is attenuated in C3 or C6 deficient mice, or in the presence of a C5 inhibitor. Increased levels of complement activation products have been demonstrated in sera of patients with aPL, though the association with clinical events remains unclear. Eculizumab, a terminal complement inhibitor, has successfully been used to treat catastrophic APS and prevent APS-related thrombotic microangiopathy in the setting of renal transplant. However, the mechanisms of complement activation in APS, its role in the pathogenesis of aPL related complications in humans, and the potential of complement inhibition as a therapeutic target in APS require further study.